Ranking of the Factors Causing Cost Overrun in Infrastructural Projects of UAE - Ahmed Marey Alhammadi, Ahmed Salem; Memon, Aftab Hameed (International Journal of Sustainable Construction Engineering and Technology, 2020)
Achieving completion of the projects within stipulated cost is the fundamental requirement of any client involved in construction projects. Especially when the projects are funded by government with the revenue generated from public where it supposed to produce more development with less investment. Unfortunately, many of the construction projects fail in meeting this basic criteria globally including UAE. Hence, this study drew attention to the factors responsible for cost overrun in construction of infrastructure projects in UAE. Data was collected through structured questionnaire survey from practitioners representing the client, consultant and contractors firms involved in infrastructure projects of UAE. Investigation involved 27 common factors categorized in three groups as design & planning related factors, management related factors and resource related factors. With the statistical analysis of 59 completed survey forms, it was revealed that lack of coordination at design phase, uncompleted design on the tender's time and frequent design changes are top 3 factors in design and planning group while in management group top 3 factors causing cost overrun are poor supervision and timely instruction from contractor, contractual claims (ex. extension of time with cost claims) and poor site management. Contractor's financial constraints, poor labour productivity and resource deficiency and shortage of technical personnel (skilled labour) are reported as major resource related factor causing cost overrun in infrastructural projects of UAE. The practitioner should work out for controlling these factors to complete the projects within the stipulated cost and avoid cost overrun.